Paul Rusesabagina's Efforts to Save the Citizens from Ethnic Conflict Reflected in Hotel Rwanda Movie (2004) by Terry George: An Individual Psychological Approach - KHUSAIN, JAMALUDIN (2012)
The major problem of this study is to reveal how Paul Rusesabagina's efforts to save the citizens from ethnic conflict reflected in Hotel Rwanda movie. The objective of this study is to analyze the movie based on its structural elements and an individual psychological approach. In analysis, the writer uses qualitative method. The object of the study is Hotel Rwanda written by Terry George. The data sources consist of primary and secondary data sources. The primary data source is Hotel Rwanda movie itself and the secondary data sources are the other sources related to the primary data such as the information about the director's biography, websites, and the other sources related to the analysis like theory of individual psychological by Alfred Adler. The method of the data collection are watching the movie, taking notes the important data, arranging the data based on category of elements of literature review, and the last is looking for the supporting data. The technique of data analysis is descriptive analysis. The outcome of the study is shown in the following conclusions. First, Terry George wants to describe that people have to try and not give up to reach something what they want with effort, prayer, and patience. Second, based on individual psychological analysis, Terry George wants to reflect that efforts of Paul Rusesabagina to save the citizens from ethnic conflict can produce happiness.